Sustainable Nutritional Strategies for Gut Health in Weaned Pigs: The Role of Reduced Dietary Crude Protein, Organic Acids and Butyrate Production - Kathryn Ruth Connolly; Torres Sweeney; John V. O’Doherty (Animals)
Weaning in piglets presents significant physiological and immunological challenges, including gut dysbiosis and increased susceptibility to post-weaning diarrhoea (PWD). Abrupt dietary, environmental, and social changes during this period disrupt the intestinal barrier and microbiota, often necessitating antimicrobial use. Sustainable dietary strategies are critical to addressing these issues while reducing reliance on antimicrobials. Reducing dietary crude protein mitigates the availability of undigested proteins for pathogenic bacteria, lowering harmful by-products like ammonia and branched-chain fatty acids, which exacerbate dysbiosis. Organic acid supplementation improves gastric acidification, nutrient absorption, and microbial balance, while also serving as an energy-efficient alternative to traditional grain preservation methods. Increasing intestinal butyrate, a key short-chain fatty acid with anti-inflammatory and gut-protective properties, is particularly promising. Butyrate strengthens intestinal barrier integrity by upregulating tight junction proteins, reduces inflammation by modulating cytokine responses, and promotes anaerobic microbial stability. Exogenous butyrate supplementation via salts provides immediate benefits, while endogenous stimulation through prebiotics (e.g., resistant starch) and probiotics promotes sustained butyrate production. These interventions selectively enhance butyrate-producing bacteria such as Roseburia and Faecalibacterium prausnitzii, further stabilising the gut microbiota. Integrating these strategies can enhance gut integrity, microbial resilience, and immune responses in weaned piglets. Their combination offers a sustainable, antimicrobial-free approach to improving health and productivity in modern pig production systems.